2022
DOI: 10.1111/epi.17223
|View full text |Cite
|
Sign up to set email alerts
|

Sustained seizure freedom with adjunctive brivaracetam in patients with focal onset seizures

Abstract: The maintenance of seizure control over time is a clinical priority in patients with epilepsy. The aim of this study was to assess the sustained seizure frequency reduction with adjunctive brivaracetam (BRV) in real‐world practice. Patients with focal epilepsy prescribed add‐on BRV were identified. Study outcomes included sustained seizure freedom and sustained seizure response, defined as a 100% and a ≥50% reduction in baseline seizure frequency that continued without interruption and without BRV withdrawal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Effectiveness outcomes included sustained seizure response (SSR) and sustained freedom (SSF); seizure worsening (greater than 25% increase in monthly seizure frequency relative to baseline) and treatment discontinuation at 12 months were also considered. Sustained seizure response (freedom) was defined as a reduction of at least 50 (100%) in baseline seizure frequency that continued without interruption from the first time it was achieved through the 12-month follow-up without BRV withdrawal in patients with at least one seizure during the 3 months before introducing BRV; the time of achievement of SSR and SSF was established using data at visits at 3, 6, and 12 months [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effectiveness outcomes included sustained seizure response (SSR) and sustained freedom (SSF); seizure worsening (greater than 25% increase in monthly seizure frequency relative to baseline) and treatment discontinuation at 12 months were also considered. Sustained seizure response (freedom) was defined as a reduction of at least 50 (100%) in baseline seizure frequency that continued without interruption from the first time it was achieved through the 12-month follow-up without BRV withdrawal in patients with at least one seizure during the 3 months before introducing BRV; the time of achievement of SSR and SSF was established using data at visits at 3, 6, and 12 months [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Simple and multivariable logistic regression models were performed to identify baseline characteristics of patients associated with SSR and SSF. Selected independent variables were age, number of concomitant ASMs, concomitant use of sodium channel blockers (SCBs), baseline monthly seizure frequency, and early add-on treatment with BRV [ 11 , 12 ]. Carbamazepine, phenytoin, lamotrigine, oxcarbazepine, eslicarbazepine acetate, lacosamide, and rufinamide were classified as SCBs; patients in the SCB group were those receiving at least one SCB, whereas those in the no-SCB group did not take any SCB.…”
Section: Methodsmentioning
confidence: 99%
“…Age, duration of epilepsy, and number of concomitant ASMs were selected as independent variables of the multivariate models for their well-known association with seizure outcomes. [9][10][11] Data analysis was performed using Stata/IC 13.1 (StataCorp). The study is reported according to STROBE guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Simple and multivariate logistic regression models were performed to evaluate whether baseline seizure frequency (<5, 5–20, and >20 seizures per month) and number of prior ASMs (<5 and ≥6) were associated with SSF and SSR. Age, duration of epilepsy, and number of concomitant ASMs were selected as independent variables of the multivariate models for their well‐known association with seizure outcomes 9–11 . Data analysis was performed using Stata/IC 13.1 (StataCorp).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation